Experiences and needs of carers of Aboriginal children with a disability: a qualitative study - Michelle DiGiacomo; Anna Green; Patricia Delaney; John Delaney; Patrick Patradoon-Ho; Patricia Mary Davidson; Penelope Abbott (BMC Family Practice, 2017)
Abstract Background Australian parents/carers of a person with a disability experience higher rates of depression, more financial stress, and are twice as likely to be in poor physical health than the general population. Aboriginal and Torres Strait Islander peoples experience worse health, social and economic outcomes than other Australians, and those with a disability face ‘double disadvantage’. This study aimed to better understand the experiences and needs of parents/carers/families of Aboriginal children with a disability. Methods Semi-structured in-depth interviews were conducted with parents or primary carers of Aboriginal children aged zero-eight with disability. Interviews were analysed using thematic analysis. Results Nineteen women (sixteen mothers and three grandmothers) were interviewed. More than half were lone carers (without a partner or spouse). Participants described their experiences, including challenges and facilitators, to providing and accessing care, impacts on their health and wellbeing, and associated economic and non-economic costs of caregiving. Financial strain and social isolation was particularly prominent for lone carers. Conclusions Tailoring services to the needs of carers of Aboriginal children with a disability means supporting kinship caregiving, facilitating engagement with other Aboriginal families, and streamlining services and systems to mitigate costs. The experiences described by our participants depict an intersection of race, socio-economic status, gender, disability, and caregiving. Services and funding initiatives should incorporate such intersecting determinants in planning and delivery of holistic care.